Responses to romidepsin by line of therapy in patients with relapsed or refractory peripheral T‐cell lymphoma. (16th December 2016) - Foss, Francine; Pro, Barbara; Miles Prince, H.; Sokol, Lubomir; Caballero, Dolores; Horwitz, Steven; Coiffier, Bertrand
Abstract: Peripheral T‐cell lymphoma (PTCL) is a heterogeneous group of aggressive non‐Hodgkin lymphomas typically associated with poor prognosis. Most patients with PTCL receive chemotherapy as first‐line treatment, but many experience rapid relapse. For patients with relapsed/refractory PTCL, responses to treatment and long‐term outcomes tend to worsen with increasing lines of therapy. Romidepsin is a potent class I histone deacetylase inhibitor approved by the US Food and Drug Administration for the treatment of PTCL in patients who have received ≥1 prior therapy. A pivotal phase 2 trial of romidepsin in patients with relapsed/refractory PTCL demonstrated an objective response rate of 25% (33/130), including 15% with confirmed/unconfirmed complete response, and a median duration of response of 28 months. In the analysis presented herein, romidepsin was shown to have similar responses and long‐term outcomes in patients with 1, 2, and ≥3 prior lines of treatment, including in patients with disease refractory to the last prior therapy. Although adverse events increased with increasing lines of treatment, the rate of dose modifications and discontinuations due to adverse events was not significantly different. These data support the use of romidepsin as salvage treatment for PTCL irrespective of the number of prior therapies. Abstract : Patients with relapsed or refractory peripheral T‐cell lymphoma (PTCL) typically have a poor prognosis. Responses to treatment and long‐term outcomes tend to worsen with increasing lines of therapy. Romidepsin is a potent class 1 histone deacetylase inhibitor approved by the US FDA for the treatment of PTCL in patients who have received ≥1 prior therapies. The analysis presented here demonstrated that romidepsin had similar responses and long‐term outcomes in patients with 1, 2, and ≥3 prior lines of treatment, including in patients with disease refractory to the last prior therapy, thereby supporting the use of romidepsin for patients with relapsed or refractory PTCL regardless of the number of prior therapies.